Studi Komparasi Hasil Belajar Siswa Melalui Strategi Pembelajaran Two Stay Two Stray Dengan Strategi Pembelajaran Team Quiz Pada Mata Pelajaran Ekonomi KelasXI SMANegeri 1 Kartasura Tahu Ajaran 2015/2016 - Bara, Sri Adma Nusa (2016)
This study aimed to test whether there are differences in learning outcomes between the use of learning strategies with two stay two stray quiz team. The subjects in this study were students of class XI SMA Negeri 1 Kartasura in the academic year 2015/2016. Class XI IPS 3 includes 33 students as an experimental group treated with the teaching learning strategies two stay two stray and class XI IPS 4 includes 33 students as a control group treated with quiz team learning strategies. Methods of data collection is done through tests and documentation. To test instrument using validity and reliability of the test. Techniques of data analysis prerequisite test using test of normality and homogeneity. Data analysis techniques to test this hypothesis using t-test. The results showed differences in learning outcomes between the economic subjects that students learn to use learning strategies with two stay two stray students who learn to use learning strategies quiz team. It can be seen from the average value of class XI IPS 3 as the experimental group using learning strategy two stay two stray is 73.79. While the average value of class XI IPS 4 as a control group using learning strategy team quiz is 81.21. The study concluded that there are differences in learning outcomes of economic subjects by using a class XI student learning strategies quiz team is better than using a learning strategy two stay two stray.